Looking for central tendencies in the conformational freedom of proteins using NMR measurements. (16th January 2017) - Clarelli, Fabrizio; Sgheri, Luca
Abstract: We study the conformational freedom of a protein made by two rigid domains connected by a flexible linker. The conformational freedom is represented as an unknown probability distribution on the space of allowed states. A new algorithm for the calculation of the maximum allowable probability is proposed, which can be extended to any type of measurements. In this paper we use pseudo contact shifts and residual dipolar coupling. We reconstruct a single central tendency in the distribution and discuss in depth the results.